(untitled) (Applied Biological Research, 2011)
The present studies on in vitro propagation of sweet cherry rootstock ‘Mazzard’ was carried out in Biotechnology laboratory, Division of Pomology, Shalimar during 2006-2009. Surface sterilization of shoot tip explants with 0.1% HgCl2 for 10 minutes yielded maximum aseptic cultures and explant survival. Using explants from forced stock plant cuttings significantly improved both these parameters. Maximum explant establishment (76.0%) was observed on MS medium supplemented with BAP + kinetin (0.25 + 0.25 mg L-1). The established explants were sub-cultured within 3 to 5 weeks of culture initiation for proliferation through stimulation of axillary buds. BAP + kinetin (0.25 + 0.25 mg L-1) accounted for maximum proliferating cultures (99.98%) with highest multiplication efficiency in terms of proliferation grade (4.0) and shoot number explant-1 (16.2). Rooting experiments were carried out by incubation of micro-shoots in IBA supplemented MS media for 10 days under darkness followed by their transfer to hormone-free MS media with incubation under light conditions of culture room. Micro-shoots greater than 10 mm in length gave maximum rooting. IBA (2.5 mg L-1) was found best auxin concentration which not only gave highest rooting (96.66%) but also maximized root number shoot-1 (6.30) and root length (48.33 mm).